1993
DOI: 10.1017/s0022215100125411
|View full text |Cite
|
Sign up to set email alerts
|

The behaviour of tympanic membrane perforations in tissue culture: a scanning electron microscopic study

Abstract: The effects of keeping rat tympanic membranes with an artificially made pars tensa perforation in tissue culture were observed under a scanning electron microscope. After one day and onwards, spreading and thickening of the keratinizing, outer squamous epithelium (OE) was noted. In addition, ballooning of the innermost cells of the outer epithelium apposing the inner tympanic epithelium (IE) was seen. No appreciable reaction was noted in the connective tissue layer of the drum. The inner tympanic epithelium ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 9 publications
0
14
0
Order By: Relevance
“…It was found that without this support, only local hyperplasia and thickening occurred without covering the perforation. 23 In the nonperforated part of the TM, proliferation in the submucosal layer has been observed to increase the thickness of whole TM. 25 In this study, this increase in thickness was mainly seen in the fibrous layer.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was found that without this support, only local hyperplasia and thickening occurred without covering the perforation. 23 In the nonperforated part of the TM, proliferation in the submucosal layer has been observed to increase the thickness of whole TM. 25 In this study, this increase in thickness was mainly seen in the fibrous layer.…”
Section: Discussionmentioning
confidence: 99%
“…15,23 The maximum proliferative response of the basal cell layer has been described as 2 mm away from the wound edge, 24 or otherwise described as 30 cells away from the perforation margin. 20 The mitotic activity of the squamous epithelium has been described differently in various reports.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to wound healing in other tissues, mitotic activity is not only confined to the wound edges but can be seen throughout the pars tensa, with the highest activity seen around the annulus and 2 mm away from the wound edges and, to a lesser degree, around the manubrium. This distant migration is further suggested by the lack of proliferative basal cells in the wound edges, which normally would be very active in other tissues 182‐185 …”
Section: Pathologic Tympanic Membranementioning
confidence: 98%
“…The most accepted theory of TM perforation healing is closure via proliferation of the TM's epidermal layer 16. The wound edge in the TM lacks the proliferative basal cell layer, providing evidence that there is a distant origin for epithelium,17, 18 whereas conventional wounds show intense mitotic activity at the wound edge. Gladstone et al15 describe the TM as displaying mitotic activity from a distant center and that mitotic activity at the wound edge occurs later and is less intense in TM wound healing, although it has been reported as early as 2 hours following perforation 19…”
Section: Introductionmentioning
confidence: 99%